Pengaruh Earning Per Share (EPS), Debt to Equity Ratio (DER) dan Return On Equity (ROE) Terhadap Harga Saham Pada Sub Sektor Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2012-2016 - Fani Selanica (Science of Management and Students Research Journal (SMS), 2019)
The purpose of this research is to know the influence of EPS, DER and ROE against stock price in simultaneously and partially on the sub sector of property and real estate eisted on the Indonesia stock exchange on periode 2012-2016.This research is a desciptive quantitative research and analysis tool used in this research are multiple linear regression is useful to see the direction of the relationship between the variable bound against free. For the purpose of answering the number one used statistical test i.e test F and to answer the purpose number 2 used statistical test i.e test t. The correlation coefficient to know how the relationship between variables and coefficients of determination of useful to see the magnitude of the influence of the variable bound against free.Property business currently provides enough opportunities and opportunities open to developing. Some of the factors that affected it between its procurement of home is always less than the needs of the community.Result SPSS 20 get a multiple linear regression equation is Log Y 1,473 + 0,462 X1 – 0,166 X2 + 0,505 X3 + e. The corellation is 0,768, meaning that is a EPS (X1), DER (X2) and ROE (X3) of stock price (Y) at on the sub sector of property and real estate eisted on the Indonesia stock exchange on periode 2012-2016.From the result of the obtained values SPSS (coefficient) r2 this figure amounted 59% states that the variable EPS, DER and ROE against of stock price is able to explain the variabel sales by 95% and the reaining 41% is explained by other factors which is not included in the research model.Simultaneously EPS, DER and ROE have a significant affect on stock price  on the sub sector of property and real estate eisted on the Indonesia stock exchange on periode 2012-2016 and partially DER and ROE has no influence on stock price on the sub sector of property and real estate eisted on the Indonesia stock exchange on periode 2012-2016.